CLINICAL AND HISTOPATHOLOGICAL CONSIDERATIONS ON THE HALLOPEAU-SIEMENS DISEASE (RDEB-HS) -A CASE REPORT - Cristina Popa; A.M. Filioreanu; C. Stelea; G. A. Maftei; E. Popescu (Romanian Dental Association for Education, 2018)
Epidermolysis bullosa is a group of genetically transmitted rare conditions characterized by tegumentary fragility, lesions on oral mucosa and dental caries. This autosomal disease includes three types of manifestations depending on the histopathological location of the lesions: simplex type-intraepidermic, jonctional - at the epidermis limit and distrophic - going beyond the structure of the dermis. Epidermolysis bullosa also includes the autosomal recessive subtype or Hallopeau-Siemens disease (RDEB-HS) characterized by severe oral mucosal lesions, such as blisters, ulcerations, scars, triggered by minor trauma (mastication of solid food). Oral cavity lesions vary in severity and frequency, ranging from small vesicles and up to eroding bullas, leaving large ulcerative areas in mucosa. The consequence is the appearance of sclero-atrophic scars in oral mucosa, resulting in a size reduction of the oral vestibule, ankyloglossy, microstomia, the occurrence of esophageal, pharyngeal or even malignant degeneration of residual lesions. In the dental tissues, the disease is manifested by the predisposition to the appearance of carious lesions, or enamel mineralization defects - imperfect amelogenesis. Material and method: This study analyzes, using clinical and histopathological criteria, the case of an 11-year-old patient diagnosed with Hallopeau-Siemens dystrophic epidermolysis bullosa. In this context, the authors investigated both tegumentary and oral cavity lesions. Results: The extraoral clinical examination reveals the presence of multiple vesicular-bullous lesions located all over the tegumentary surface, including the cephalic extremity, followed by the occurrence of synechiae scars, accompanied in the upper limbs by pseudo-syndactilia. Intraoral clinical examination reveals mucosal lesions with variable fluid contents located on the keratinized areas (the attached gum, the dorsal face of the tongue), as well as on the non-keratinized mucosa (jugal, floor of the mouth). The patient also has multiple coronary odontal lesions affecting both temporary and definitive dentition and poor oral hygiene. Conclusions: Understanding the lesion formation and manifestation mechanism, its evolution and method of healing is a priority in the treatment of patients with dystrophic epidermolysis bullosa, both for the dentist and the dento-alveolar surgeon. The tissue fragility of the oral mucosa, as well as the predisposition to the appearance of carious lesions and dental dystrophies require a specific approach to the patient in establishing the correct therapy management.